SAINT ELIJAH’S DAY IN THE VILLAGE OF RUJIŠTE: A CONTRIBUTION TO THE RESEARCH OF THE SOCIAL-INTEGRATIVE ROLE OF THE SECONDARY PATRON SAINT CELEBRATION IN IBARSKI KOLAŠIN (Heritage, 2023)
The author of this paper presents part of the results of his field research in Ibarski Kolašin, a region in the northwest of Kosovo and Metohija. Central attention is paid to the event that the Serbs from Ibarski Kolašin perceive as an important part of their traditional cultural heritage, which is the secondary family patron saint celebration. The research of the mentioned event was carried out in the village of Rujište, located in the eastern part of Ibarski Kolašin, which is characterized by the fact that all its inhabitants celebrate Saint Elijah as a secondary family patron saint. The author tries to present the main elements of the celebration of the Saint Elijah’s Day in Rujište, with a focus on a collective aspect of the celebration, while the goal of the paper is an attempt to contribute to the understanding of the researched event as a phenomenon whose important role, viewed from the aspect of demographic processes in Ibarski Kolašin, is the role of social-integrative character. The research procedure applied in the aim of achieving mentioned goal was based on the qualitative method approach, primarily observation and conversations with interlocutors. Field research for the needs of paper in the village of Rujište was conducted in August 2023.
Keywords: Saint Elijah's Day, secondary patron saint celebration, Ibarski Kolašin, Rujište, Serbs, Kosovo and Metohija